SENIOR HIGH SCHOOL STUDENTS’ RESPONSES TO GUIDED INQUIRY LEARNING MODEL - BAITY, NUR; JATMIKO, BUDI (Inovasi Pendidikan Fisika, 2018)
The development of technology and education in the 21st century is also increasing the competition in the world. Learning model that can support the competition in the 21st century one of them is guided inquiry. Therefore, this study aims to describe the responses of senior high school students to guided inquiry learning model. This research is a pre-experimental study with one group pre-test - post-test design. Research subjects used in this study are 90 students divided into three classes, namely experiment 1, experiment 2, and experiment 3. Learning devices used are syllabus, lesson plan, handout, worksheet. The research instrument used is the questionnaire of the students response questionnaire. The collected data were analyzed using responsive questionnaire analysis. The result of this research shows that in the experimental class 1 students get responses of 76.25% with good category, and in the experimental class 2 & 3 get the students response of 81.08% with very good category. The results of the students responses prove that the guided inquiry learning model is effective when applied to physics learning.